A binding-induced sutured toehold activation for controllable DNA strand displacement reactions1. Issue 14 (18th February 2015) - Zhu, Jing; Wang, Lei; Jiang, Wei
<x xml:space="preserve">Abstract</x> Leveraging upon the environmental stimuli-responsive hairpin reconfiguration, a novel toehold activation strategy for controlling the DNA strand displacement was developed.